2020
DOI: 10.1097/qad.0000000000002744
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of classic and HIV-viremic and aviremic AIDS Kaposi sarcoma

Abstract: Background: Kaposi sarcoma in people living with HIV (PLHIV) is the most common AIDS-associated malignancy. There is increased interest in Kaposi sarcoma in PLHIV with controlled HIV viremia. Objectives: To describe Kaposi sarcoma occurring in PLHIV despite virological control and to compare their clinical presentations with viremic AIDS-Kaposi sarcoma (AIDS-KS) and classic Kaposi sarcoma (CKS). Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The risk is still over 50-fold higher for PLHIV with long-term viral suppression (i.e., >2 years) than for the uninfected population [44]. Moreover, some studies have reported KS occurring in aviremic patients [45][46][47].…”
Section: Immuno-deficiency Hiv Viral Load and Cd4/cd8 Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The risk is still over 50-fold higher for PLHIV with long-term viral suppression (i.e., >2 years) than for the uninfected population [44]. Moreover, some studies have reported KS occurring in aviremic patients [45][46][47].…”
Section: Immuno-deficiency Hiv Viral Load and Cd4/cd8 Ratiomentioning
confidence: 99%
“…Classic KS are usually indolent and progress slowly while AIDS KS are more aggressive [47]. In a recent retrospective monocentric study of endemic and classic KS (29 and 131, respectively) in France, endemic KS was associated with higher risk of systemic treatment, chemotherapeutic agent or immune-modulating therapies, and initiation than classic KS [82].…”
Section: The Other Forms Of Ks: the Classic Ks And Endemic Ksmentioning
confidence: 99%
“…These cases, referred to an expert national panel for cancer treatment advise for PLHIV, probably represented the more severe cases of KS in aviremic HIV-patients in France at that time. A monocentric study from France described all consecutive diagnosed cases of KS in aviremic (12 cases) and viremic (97 cases) HIV-patients diagnosed in a tertiary referral hospital between 2000 and 2017, comparing their clinical presentations with classic KS (also named "Mediterranean KS", in HIV-negative individuals) consecutively diagnosed in the same area and extracted from the Francim cancer databank [8]. Locally skin indolent presentation was the main clinical presentation in 10 of the KS in aviremic patients, although one patient had visceral involvement and one a disseminated mucocutaneous form.…”
Section: Clinical Presentation Of Ks In Virally Suppressed Hiv-patientsmentioning
confidence: 99%
“…As KS in aviremic patients may be more commonly indolent [5,8], the use of alternative classifications from non-HIV populations is appealing. A proposed staging system derived from 300 CKS patients based on disease progression was developed [18]: stage I defined by small macules and nodules primarily confined to the lower extremities, stage II by infiltrative plaques mainly involving the lower extremities, sometimes associated with a few nodules, stage III with florid multiple angiomatous plaques and nodules involving the lower extremities that are often ulcerated, and a stage IV with disseminated disease.…”
Section: Clinical Presentation Of Ks In Virally Suppressed Hiv-patientsmentioning
confidence: 99%
See 1 more Smart Citation